2019
DOI: 10.3390/rs11202393
|View full text |Cite
|
Sign up to set email alerts
|

The Case for a Single Channel Composite Arctic Sea Surface Temperature Algorithm

Abstract: Surface temperatures derived from satellite thermal infrared (TIR) data are critical inputs for assessing climate change in polar environments. Sea and ice surface temperature (SST, IST) are commonly determined with split window algorithms that use the brightness temperature from the 11 µm channel (BT 11 ) as the main estimator and the difference between BT 11 and the 12 µm channel (BTD 11-12 ) to correct for atmospheric water vapor absorption. An issue with this paradigm in the Arctic maritime environment is … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
5
0

Year Published

2020
2020
2023
2023

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 7 publications
(5 citation statements)
references
References 28 publications
0
5
0
Order By: Relevance
“…All AVHRR data were retrieved online from NOAA's Comprehensive Large Array-Data Stewardship System [23]. Surface temperatures were determined for METOP-A AVHRR images using the single channel Composite Arctic Sea Surface Temperature Algorithm (CASSTA) [24]. In clear sky conditions CASSTA uses Channel 4 to determine the temperature of three regimes: sea surface, ice surface, and marginal ice zones containing a combination of seawater and ice.…”
Section: Satellite Datamentioning
confidence: 99%
“…All AVHRR data were retrieved online from NOAA's Comprehensive Large Array-Data Stewardship System [23]. Surface temperatures were determined for METOP-A AVHRR images using the single channel Composite Arctic Sea Surface Temperature Algorithm (CASSTA) [24]. In clear sky conditions CASSTA uses Channel 4 to determine the temperature of three regimes: sea surface, ice surface, and marginal ice zones containing a combination of seawater and ice.…”
Section: Satellite Datamentioning
confidence: 99%
“…Automated measurements from satellite observation underpinned by remotely operated vehicles, autonomous vehicles, and buoys (such as data collected from the International Arctic Buoy Programme) offers the only currently available solution to providing the necessary synoptic measurements of multiple oceanographic parameters to characterize surface environmental heterogeneity (Shutler et al, 2019). Satellite observation can be used to study environmental conditions important in polar waters (Shutler et al, 2019) including: freshwater fluxes (e.g., Nichols and Subrahmanyam, 2019); surface water temperature (e.g., Vincent, 2019); Chlorophyll-a concentration, primary production and net community production (e.g., Babin et al, 2015), and sea ice type and depth (e.g., Kwok, 2018). Recent developments have shown that satellite observation measurements of temperature and salinity can provide observational-based estimates of surface carbonate system conditions (Land et al, 2019).…”
Section: Establish Baselinesmentioning
confidence: 99%
“…Compared with traditional in situ measurements, remote sensing technology has the advantages of low cost, wide coverage, and rapid updating. The emergence of remote sensing techniques has facilitated the detection of changes occurring on the Earth on a steady basis, such as monitoring the variation of Arctic sea ice and providing an opportunity to gain a deeper insight into surface temperature changes in the Arctic [8][9][10][11].…”
Section: Introductionmentioning
confidence: 99%
“…Many scholars have studied surface temperature retrieval within the Arctic sea ice region utilizing thermal infrared imagery acquired by satellite-borne thermal infrared sensors, such as Terra and Aqua/moderate resolution imaging spectroradiometer (MODIS), advanced very high-resolution radiometer (AVHRR), and advanced spaceborne thermal emission and reflection radiometer (ASTER), etc., to improve the understanding of climate change in the Arctic [9,[11][12][13][14]. Surface temperature quantification in the Arctic ice-water mixture zone (IWMZ) faces several challenges due to large inter-annual and intra-annual fluctuations in sea ice coverage and the complexity of the sea ice and water mixture [15,16].…”
Section: Introductionmentioning
confidence: 99%